Ethylene-Induced Flavonol Accumulation in Guard Cells Suppresses Reactive Oxygen Species and Moderates Stomatal Aperture. Issue 4 (4th March 2014) - Watkins, Justin M.; Hechler, Paul J.; Muday, Gloria K.
Abstract : In the epidermis of Arabidopsis leaves, flavonols specifically accumulate in guard cells with enhanced synthesis in the presence of ethylene, where they lower the levels of reactive oxygen species and reduce the rate of stomatal closure . Abstract: Guard cell swelling controls the aperture of stomata, pores that facilitate gas exchange and water loss from leaves. The hormone abscisic acid (ABA ) has a central role in regulation of stomatal closure through synthesis of second messengers, which include reactive oxygen species (ROS ). ROS accumulation must be minimized by antioxidants to keep concentrations from reaching damaging levels within the cell. Flavonols are plant metabolites that have been implicated as antioxidants; however, their antioxidant activity in planta has been debated. Flavonols accumulate in guard cells of Arabidopsis thaliana, but not surrounding pavement cells, as visualized with a flavonol-specific dye. The expression of a reporter driven by the promoter of CHALCONE SYNTHASE, a gene encoding a flavonol biosynthetic enzyme, in guard cells, but not pavement cells, suggests guard cell-specific flavonoid synthesis. Increased levels of ROS were detected using a fluorescent ROS sensor in guard cells of transparent testa4-2, which has a null mutation in CHALCONE SYNTHASE and therefore synthesizes no flavonol antioxidants. Guard cells of transparent testa4-2 show more rapid ABA -induced closure than the wild type, suggesting that flavonols may dampen the ABA -dependent ROS burst that drives stomatal closing. The levels of flavonols are positively regulated in guard cells by ethylene treatment in the wild type, but not in the ethylene-insensitive2-5 mutant. In addition, in both ethylene-overproducing1 and ethylene-treated wild-type plants, elevated flavonols lead to decreasing ROS and slower ABA -mediated stomatal closure. These results are consistent with flavonols suppressing ROS accumulation and decreasing the rate of ABA -dependent stomatal closure, with ethylene-induced increases in guard cell flavonols modulating these responses.